Pengembangan Bahan Ajar E-Learning Berbasis Edmodo pada Materi Litosfer Kelas X SMA - Dedi Sasmito Utomo; Sumarmi Sumarmi; Singgih Susilo (Universitas Negeri Malang, 2015)
Abstract: The objective of this research and development is to produce: (1) E learning materials based on the material Edmodo lithosphere grade X, (2) virtual classroom Edmodo, and (3) Edmodo guide books for teachers and students. Data were collected by using a validation sheet and questionnaire. Qualitative data are derived from expert validation of material, language, and learning design, while quantitative data derived from student questionnaires. Results of the research are: (1) E learning instructional materials contained in the web categorized of well, (2) the virtual classroom Edmodo contained at the http://edmodo.com/dedisasmito, and (3) guide book Edmodo entitled